CUSTOMER ENGAGEMENT DALAM MOBILE MARKETING DAN CONTENT MARKETING - Alhidayatullah Alhidayatullah (Program Studi Magister Manajemen, Direktorat Pascasarjana, Universitas Sangga Buana, 2024)
The purpose of this study is to examine and elucidate how content marketing and mobile marketing affect consumer engagement. This study's research methodology is associative and quantitative in nature. One hundred respondents who were customers of Ghaisan Boutique Sukabumi Online Retail made up the study's sample. Using Google Forms, questionnaires were sent directly to Ghaisan Boutique Sukabumi Online Retail customers to collect study data. Multiple linear regression analysis is the analytical method employed in this work. The study's findings demonstrated that factors related to mobile marketing positively impact client engagement. Customer engagement is positively impacted by mobile and content marketing elements to the tune of 50%, with the other 50% being influenced by unstudied variables. This study adds to the body of knowledge in marketing management about consumer involvement, content marketing, and mobile marketing in the context of marketing.